Analysis of design process of automated fire protection system - Sotnik, S. V.; Vasylchenko, Y. R. (ХНУРЕ, 2023)
This work addresses topical issue of fire safety, identifying its importance in various spheres of life and emphasizing potential threats to people and property. The importance of automating fire safety systems and developing modern fire protection systems (FPS) as key element for minimizing risks and responding effectively to fire situations is discussed. The work provides details of fire protection system design process, including choice of system type, equipment brand, integration with other systems, and development of equipment layouts. Taking into account the various features of facilities, work recommends optimal approaches to selection and development of fire alarm system, helping to ensure complete control and safety at facilities of various nature.
QR codes in production
Keywords: fire alarm; detector; protection systems